In Vitro Drug Release and Study of Anti-inflammatory Effect of Rasna Saptak Kwath - Pandey, Shruti (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: Rasna Saptak Kwatha is an Ayurvedic formulation used orally to relieve inflammation and pain in arthritis. It has seven ingredients, namely, Pluchea lanceolata, Tribulus terrestris, Tinospora cordifolia, Boerhavia diffusa, Ricinus communis, Cedrus deodara, and Cassia fistula. The Zingiber officinale is used as additives at the time of administration. Materials and Methods: All these herbs were mixed together and making decoction and hydroalcoholic extraction of Rasna Saptak Kwatha churna. After that permeability of drug was checked as a membrane. Result and Discussion: The in vitro experiment results showed that the drug is permeating through the skin. In the carrageenan edema model, hydroalcoholic extract showed better inhibition in comparison to aqueous extract. Conclusion: It can be concluded from the study that extracts could be served or can be modified for topical or transdermal drug delivery system.